Trends and Research Landscape of Innovative Teaching Methods for Islamic Education Teachers: A Bibliometric Analysis of Scopus Publications (2015–2025) - Adelia, Kholifah; Iryanti, Shobah Shofariyani (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2026)
.This study was motivated by the rapid development of digital technology, which has driven a paradigm shift in Islamic Religious Education. The study aims to analyze trends, productivity, and the direction of research on innovative teaching methods for IRE teachers during the period 2015–2025. The method used is bibliometric analysis with a descriptive quantitative approach to secondary data sourced from the Scopus database. A total of 331 articles were analyzed using Biblioshiny for RStudio and VOSviewer 1.6.20 through keyword co-occurrence mapping and thematic mapping. The results showed a significant increase in publications since 2019, with Indonesia as the largest contributor, followed by Malaysia and Turkey. The dominant themes included Islamic education, innovation, digital learning, blended learning, and problem-based learning. These findings confirm a shift in research focus from conventional learning approaches to the integration of Islamic values with innovations in learning technology. Theoretically, this study fills a gap in research by mapping the global landscape and direction of Islamic religious education research. In practical terms, the results of this study provide a reference for educators and researchers in developing Islamic religious education learning that is relevant to the demands of 21st-century education.